2005
DOI: 10.1504/ijcat.2005.006481
|View full text |Cite
|
Sign up to set email alerts
|

Feature ontologies for the explicit representation of shape semantics

Abstract: CAx systems typically encode the semantics of shapes as so-called parametric features on different levels of abstraction. Here we discuss an approach that combines feature-based parametric modelling with techniques from the field of knowledge representation and ontological reasoning. Parametric models refer to feature ontologies that model feature semantics on several levels of granularity. On higher levels, the interrelation between features and feature interoperability is captured whereas on lower levels a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
0
12
0
3
Order By: Relevance
“…Here, 'generic' emphasize the 'abstracted' class definition that support polymorphic definitions of features such that systematic processing methods, including repository services, validating checking routines, and change propagation, can be shared and automated. This idea is supported by some research works related to associative or resource adaptive features (Raman and Marefat 2004;Ma and Tong 2003;Ma et al 2007;Kim et al 2004), and extended feature types and ontology schemes reported Brunetti and Grimm 2005). However, none seems to have reached maturity.…”
Section: The Authors' View Of a New Paradigmmentioning
confidence: 84%
See 1 more Smart Citation
“…Here, 'generic' emphasize the 'abstracted' class definition that support polymorphic definitions of features such that systematic processing methods, including repository services, validating checking routines, and change propagation, can be shared and automated. This idea is supported by some research works related to associative or resource adaptive features (Raman and Marefat 2004;Ma and Tong 2003;Ma et al 2007;Kim et al 2004), and extended feature types and ontology schemes reported Brunetti and Grimm 2005). However, none seems to have reached maturity.…”
Section: The Authors' View Of a New Paradigmmentioning
confidence: 84%
“…In addition, non-geometric relations also exist between features and non-geometric entities. For example, at the design stage, functional-form matrixes, bipartite function-feature graphs, design flow chains, design key characteristics, and mapping hierarchies can be used to link abstracted concept features to product functions (Feng et al 1996;Mukherjee and Liu 1997;Whitney et al 1999;Brunetti and Golob 2000;Brunetti and Grimm 2005). At the process planning stage, machining features are also related to non-geometric entities, such as machines, cutting tools, and machining processes (Khoshnevis et al 1999;Sormaz and Khoshnevis 2003).…”
Section: Relations In a Feature-based Application Modelmentioning
confidence: 99%
“…De la mayor parte de las definiciones existentes y de las propuestas de EC presentes en la literatura, se desprende que los EC tienen dos características fundamentales [Ma et ál., 2008]: (1) los EC hacen referencia a la geometría del producto en un nivel superior al de las entidades geométricas y topológicas; (2) representan una intención de ingeniería. A la primera característica también hacen referencia Brunetti y Grimm [Brunetti y Grimm, 2005] cuando establecen los niveles del EC de forma (Form Feature) y los de aplicación y ensamble (Application Feature, Assembly Feature) como unos niveles superiores a los de geometría, de topología y paramétrico, en su descripción del modelo de capas en el que habitualmente se organizan los sistemas de X Asistido por Ordenador (Computer Aided X, CAX). Se trata de un modelo de capas en el que cada nivel se construye en base a los inferiores (Figura 4.1).…”
Section: Fundamentos Del Concepto De Elemento Característicounclassified
“…Se trata de un modelo de capas en el que cada nivel se construye en base a los inferiores (Figura 4.1). Brunetti y Grimm, 2005].…”
Section: Fundamentos Del Concepto De Elemento Característicounclassified
See 1 more Smart Citation